2013
DOI: 10.1039/c3sm27797f
|View full text |Cite
|
Sign up to set email alerts
|

Thin film confinement of a spherical block copolymer via forced assembly co-extrusion

Abstract: A spherical, block copolymer (BCP) with a statistical mid-block was investigated under confinement via forced assembly co-extrusion.This approach provided a continuous methodology to investigate the effect of layer thickness and substrate on the morphology of a unique self-assembling material. It was demonstrated that substrate interactions and layer thickness can promote long-range ordering for use in highly diverse nanotechnology applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
8
1
Order By: Relevance
“…SI-4). Contrary to what was observed by Burt et al [10,12,43], SAXS patterns do not show any significant change, probably due to the lack of mobility of the copolymer at this temperature (T g,PMMA + 15 • C).…”
Section: Resultscontrasting
confidence: 95%
“…SI-4). Contrary to what was observed by Burt et al [10,12,43], SAXS patterns do not show any significant change, probably due to the lack of mobility of the copolymer at this temperature (T g,PMMA + 15 • C).…”
Section: Resultscontrasting
confidence: 95%
“…Their work also showed that the packing of the cylinders was improved with the reduction of the layer thickness, especially after long times annealing [42e44]. A last article showed similar results for a spherical triblock (SEBS) extruded above T odt [46]. Nanolayer coextrusion has been developed in our lab [47e50] and also used recently to confine an asymmetric BCP poly(styreneb-butadiene-b-methyl methacrylate) (SBM) with an incompatible matrix (polycarbonate PC) [51].…”
Section: Introductionsupporting
confidence: 57%
“…Long-range order within the confined layers is achieved (and can be to some extent controlled via the processing parameters) on large scales of material through an industrially relevant process, similar to previous studies [42e44, 46,51]. More surprisingly and rarely observed experimentally (and to the best of our knowledge for the first time in a materials engineering context), it is shown that nanolayer coextrusion favors through shearing and "soft" confinement a cylindrical morphology over a lamellar one more thermodynamically favored.…”
Section: Introductionmentioning
confidence: 60%
“…Recent innovations in multilayer coextrusion have utilized this scalable, melt-processing strategy to manufacture polymer composites containing distributed domains of micro- and nanoscale fibers. , Extruded composites of rectangular PCL fibers in a PEO matrix have been investigated for relevance in biomedical applications. Uniaxial PCL/PEO composite drawing and subsequent removal of the PEO matrix yielded PCL fiber scaffolds with tunable mechanics, high surface area, and nanoscale dimensions. , Functional coextruded PCL fibers were also achieved by Kim et al via surface modification using “click” chemistry, imparting gradient density modification and multifunctionality to enhance cellular proliferation and direct differentiation along the fiber scaffolds. Although these extruded PCL fiber mats have potential in a range of biomedical applications, one can envision that this manufacturing platform may address key challenges in the development of fiber-reinforced hydrogels with synergistic mechanics due to the structural organization of these fiber/matrix coextruded composites with a distributed microscale PCL fiber architecture throughout the “sacrificial” PEO matrix.…”
Section: Introductionmentioning
confidence: 99%